PENGARUH GIRO WAJIB MINIMUM, BI RATE DAN INFLASI TERHADAP LOAN TO DEPOSIT RATIO - N, Elly Soraya; Safitri, Rika (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
The purpose of this research is to analyze the influence of Minimum statutory reserve, BIRate, and Inflation towards Loan to Deposit Ratio. Population in this research used JointVenture Bank in Indonesian Banking Directory during period 2013 through 2017.Purposive sampling method were used as samples determining method and 14 bankselected as the sample of the research. This type of research is descriptive quantitative.Presentation and analysis of research data using descriptive statistical analysis, paneldata regression models, data estimation methods namely Chow Test, classicalassumption analysis using normality test, multicollinearity test and hypothesis test. Thisresult of research show that variable GWM have positive and not significant influence toLDR. Variable BI Rate have negative significant influence to LDR. And variable inflationhave positive significant influence to LDR. The coefficient of determination (R2) is 89%compared to the independent variable on the variable Loan to Deposit Ratio in 2013-2017. While 4% is contributed by other factors.